Rel-dependent decrease in the expression of ribosomal protein genes by inhibition of the respiratory electron transport chain in Mycobacterium smegmatis - Kim, Na-Kyeong; Baek, Jong-Eun; Lee, Ye-Jin; Oh, Yuna; Oh, Jeong-Il (Frontiers in Microbiology, 2024)
In this study, we demonstrated that both the expression of most ribosomal protein genes and the amount of ribosomes were decreased in the Δaa3 mutant of Mycobacterium smegmatis, in which the major terminal oxidase (aa3 cytochrome c oxidase) of the respiratory electron transport chain (ETC) is inactivated, compared to those in the wild-type strain. Deletion of the rel gene encoding the major (p)ppGpp synthetase in the background of the Δaa3 mutant restored the reduced expression of ribosomal protein genes, suggesting that inhibition of the respiratory ETC leads to the Rel-dependent stringent response (SR) in this bacterium. Both a decrease in the expression of ribosomal protein genes by overexpression of rel and the increased expression of rel in the Δaa3 mutant relative to the wild-type strain support the Rel-dependent induction of SR in the Δaa3 mutant. We also demonstrated that the expression of ribosomal protein genes was decreased in M. smegmatis exposed to respiration-inhibitory conditions, such as KCN and bedaquiline treatment, null mutation of the cytochrome bcc1 complex, and hypoxia. The MprBA-SigE-SigB regulatory pathway was implicated in both the increased expression of rel and the decreased expression of ribosomal protein genes in the Δaa3 mutant of M. smegmatis.